Working virtually challenges of virtual teams - Jones, Robert, 1955 Feb. 11-; Oyung, Robert, 1966-; Pace, Lise, 1964-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This book provides an in-depth, practical perspective on the growing dependence of virtual teams and how to best exploit them. Based on years of direct experience in managing and participating in virtual teams, as well as developing solutions to help virtual teams be more effective, the authors have provided unique insight that can be leveraged to help you get the most of your virtual teams.
I. Eight myths of virtual teams -- II. Look them straight between the eyes -- III. Out of sight, out of mind -- IV. It's the exception, not the norm -- V. Establishing trust -- VI. Show me the money -- VII. Human resources advantages -- VIII. Organizational advantages -- IX. Mostly co-lated -- X. Mostly virtual -- XI. How teams work virtually -- XII. International issues -- XIII. Virtual team maturity curve -- XIV. Where is your company or organization on the virtual team continuum? -- XV. Managing a virtual team -- XVI. Managing a virtual organization -- XVII. Impact of culture, affiliation, and shared goals -- XVIII. Evolution of the groupware concept -- XIX. Applying tools for maximum impact -- XX. Team building -- XXI. The challenges of virtual teams -- XXII. The virtual organization -- XXIII. A virtual ecosystem -- XXIV. E-lancing -- XXV. Kids of the internet generation -- XXVI. Virtually meeting five-year vision/narrative -- XVII. Do virtual teams ever need to meet face-to-face?
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 25, 2010).
Keywords: Virtual work teams; Teams in the workplace -- Computer networks; Virtual reality in management; Electronic books